nizomova_zebo@jspi.uz THE PROBLEM OFALLITERATION IN ENGLISH LITERATURE: THE PROBLEM OFALLITERATION IN ENGLISH LITERATURE - Nizomova, Zebo (Журнал иностранных языков и лингвистики, 2022)
It is known that for the perception of a literary work in its entirety, it is important to be able not only to “read” information, but also to feel the style of the writer, where stylistic devices play a huge role, some of which affect the human subconscious. These techniques include alliteration and assonance, which can enhance the emotional impact on the reader. From this point of view, this article deals with the issues of the problem and the role of alliteration in English literature.